The role of architects in earthquake-resistance in buildings locally (Damascus University Journal for engineering sciences, 2022)
Earthquakes are considered one of the greatest natural hazards the globe has witnessed, due to the catastrophic and devastating aftermath on buildings and infrastructures in multiple regions. This is what prompted engineering sciences to study and analyze this phenomenon, to find standards and systems for construction, design and implementation of facilities, and to develop a controlled engineering methodology under the name of earthquake engineering    The seismic design of the building begins with the architect’s initial studies, with the aim of achieving the basic architectural requirements, and producing balanced architectural configurations that contribute to raising the building’s performance against earthquakes. This might happen through creative design solutions that match the functional program of the building, and using architectural vocabulary that complements the structural system to achieve durability and stability, and its aesthetic appearance as well.   This research aims to measure the knowledge of seismic requirements and standards amongst local architects, and to review the most important architectural and constructional considerations which affect the performance of the building, and to study some global examples that have benefited from earthquake-resistant structural elements with distinctive designs, to analyze the results of the questionnaire distributed to architects in order to monitor the level of awareness of the influence of architectural design on stability of the building, to reach proposals that help increase the knowledge of the architects regarding seismic considerations and requirements.
Keywords: seismic architecture; non-structural elements; load paths; structural elements; seismic requirements